Peran Mahasiswa dalam Edukasi Anti Korupsi: Pengabdian kepada Masyarakat Berbasis Service Learning - Afandi, Muhamad Ridwan; Rizqullah, Muhammad Naufan (Bahasa Indonesia, 2025)
Corruption remains a serious challenge in realizing clean and accountable governance in Indonesia. Higher education institutions play a strategic role in instilling anti-corruption values through the curriculum, as mandated by Regulation of the Ministry of Research, Technology, and Higher Education No. 33 of 2019. This study aimed to equip students with both knowledge and practical experience in anti-corruption education through a service learning approach. The program involved 20 students of the Environmental Health Study Program at Universitas Sriwijaya under the guidance of two field supervisors, implemented at two secondary schools: SMAN 1 Indralaya (representing a suburban context) and SMAN 15 Palembang (representing an urban context). The activities were conducted in three stages: pre-implementation (classroom learning and action planning), implementation (counseling and socialization using presentations, posters, and interactive games), and post-implementation (evaluation through pre-tests, post-tests, and feedback questionnaires). The results showed a significant increase in students’ knowledge and awareness, with 97% of participants stating that the program was beneficial and 100% committing to uphold integrity values and reject corruption. This program not only strengthened awareness among secondary school students but also enhanced university students’ skills in communication, leadership, and integrity values. Thus, integrating anti-corruption education through service learning provides a concrete contribution to shaping student change agents in society’s collective effort to prevent corruption.   Abstrak Korupsi masih menjadi persoalan serius dalam upaya mewujudkan tata pemerintahan yang bersih dan berintegritas di Indonesia. Perguruan tinggi memiliki peran strategis dalam menanamkan nilai antikorupsi melalui kurikulum, sebagaimana diamanatkan dalam Permenristekdikti No. 33 Tahun 2019. Penelitian/pengabdian ini bertujuan membekali mahasiswa dengan pengetahuan sekaligus pengalaman praktis dalam edukasi antikorupsi melalui pendekatan service learning. Kegiatan dilaksanakan oleh 20 mahasiswa Program Studi Kesehatan Lingkungan Universitas Sriwijaya dengan bimbingan dua dosen lapangan di dua sekolah menengah, yaitu SMAN 1 Indralaya (pinggiran) dan SMAN 15 Palembang (perkotaan). Metode pelaksanaan meliputi tahap pra-implementasi (pembelajaran kelas dan perencanaan aksi), implementasi (penyuluhan dan sosialisasi dengan media presentasi, poster, dan permainan interaktif), serta pasca-implementasi (evaluasi melalui pre-test, post-test, dan kuesioner umpan balik). Hasil menunjukkan peningkatan signifikan pengetahuan dan kesadaran siswa, dengan 97% peserta menyatakan kegiatan bermanfaat dan 100% berkomitmen menolak praktik korupsi. Kegiatan ini tidak hanya memperkuat pemahaman pelajar, tetapi juga mengembangkan keterampilan komunikasi, kepemimpinan, dan nilai integritas mahasiswa. Dengan demikian, integrasi pendidikan antikorupsi melalui service learning berimplikasi nyata dalam membentuk agen perubahan yang berkontribusi pada upaya pencegahan korupsi di masyarakat.